Transtornos mentais comuns e atividade física no lazer entre residentes de áreas urbanas de Feira de Santana – Bahia - Rocha, Saulo Vasconcelos (2009)
Introduction. Common mental disorders characterized by symptoms such as insomnia, fatigue, irritability, forgetfulness, difficulty concentrating, and somatic complaints, constitute a major public health problem. Research on mental disorders raises important questions about the understanding, nature and course of these disorders and the possibility of including other mechanisms aids in the prevention and treatment, for example, the practice of regular physical activity. Objective. To analyze the relationship between physical activity during leisure time and mental disorders and to describe the prevalence of common mental disorders according to sociodemographic characteristics, behavioral and medical conditions among residents in urban areas of Feira de Santana, Bahia.. Methods. Epidemiological study of cross-sectional representative sample of 3597 individuals, 71.4% female and 28.6% of male urban population of Feira de Santana- BA over the age of 15 years. We used a standardized questionnaire containing sociodemographic information, diseases, screening for mental disorders and lifestyle habits. Statistical analysis was performed with significance level p _ 0.05, with calculation of their prevalence ratios and confidence intervals. Results. We found a frequency of 72.3% of individuals considered insufficiently active leisure. The prevalence of CMD was 29.9%, From the stratified analysis, there was a significant association of CMD with sociodemographic variables, lifestyle and medical conditions.Conclusion. The use of tobacco, enough time for leisure and leisure-time physical inactivity are associated with higher prevalence of CMD. These findings stimulate discussion about the need to implement public policies to create spaces for the practice of leisure activities and campaigns to combat tobacco use.